HRP2–DPF3a–BAF complex coordinates histone modification and chromatin remodeling to regulate myogenic gene transcription. Issue 12 (27th May 2020) - Zhu, Xu; Lan, Bingxue; Yi, Xianfu; He, Chaoran; Dang, Lin; Zhou, Xingquan; Lu, Yumei; Sun, Yongzhan; Liu, Zhiheng; Bai, Xue; Zhang, Kai; Li, Bing; et al.
Abstract: Functional crosstalk between histone modifications and chromatin remodeling has emerged as a key regulatory mode of transcriptional control during cell fate decisions, but the underlying mechanisms are not fully understood. Here we discover an HRP2–DPF3a–BAF epigenetic pathway that coordinates methylated histone H3 lysine 36 (H3K36me) and ATP-dependent chromatin remodeling to regulate chromatin dynamics and gene transcription during myogenic differentiation. Using siRNA screening targeting epigenetic modifiers, we identify hepatoma-derived growth factor-related protein 2 (HRP2) as a key regulator of myogenesis. Knockout of HRP2 in mice leads to impaired muscle regeneration. Mechanistically, through its HIV integrase binding domain (IBD), HRP2 associates with the BRG1/BRM-associated factor (BAF) chromatin remodeling complex by interacting directly with the BAF45c (DPF3a) subunit. Through its Pro-Trp-Trp-Pro (PWWP) domain, HRP2 preferentially binds to H3K36me2. Consistent with the biochemical studies, ChIP-seq analyses show that HRP2 colocalizes with DPF3a across the genome and that the recruitment of HRP2/DPF3a to chromatin is dependent on H3K36me2. Integrative transcriptomic and cistromic analyses, coupled with ATAC-seq, reveal that HRP2 and DPF3a activate myogenic genes by increasing chromatin accessibility through recruitment of BRG1, the ATPase subunit of the BAF complex. Taken together, these results illuminate a key role for the HRP2-DPF3a-BAF complex in the epigenetic coordination of gene transcription during myogenic differentiation.